2011
DOI: 10.1007/s00044-011-9644-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial activity of 5-chloroindoline-2,3-dione derivatives

Abstract: A series of 3-(5-chloro-2-oxoindolin-3-ylideneamino)-2-arylthiazolidin-4-ones 4a-k and 5-chloro-3-(3-chloro-2-oxo-4-arylazetidin-1-ylimino)indolin-2-ones 5a-k was synthesized. The structures of final compounds were confirmed by analytical (C, H, N) and spectral (FT-IR, 1 H NMR, 13 C NMR and Mass) data. The synthesized compounds were screened for possible antibacterial and antifungal activity. Compounds 4c, 4f, 4g, 4h, 4i, 4j, 5c, 5f, 5g, 5h, 5i and 5j showed substantially significant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The IR spectra of compounds 4a-o displayed absorption bands around 3400 cm -1 for the indolic NH group in addition to the absorption bands of carbonyl groups near 1720 cm -1 which is consistent with the previously reported ones for compounds 4a [26] and 4f [27]. Also, their 1 H NMR spectra revealed a D 2 O-exchangeable signals in the region δ 10.84-11.01 ppm attributable to the NH protons of the indolin-2-one moieties, in addition to the signal of the methine protons (-CH = N-) in the region δ 8.55-8.70 ppm which is in accordance with those previously reported for compounds 4a [26], 4f [27] and 4i [28]. Moreover, the 13 C NMR spectra of compounds 4a-o showed signals resonating around δ 163 ppm, characteristic of C = O carbons.…”
Section: Results and Discussion Chemistrysupporting
confidence: 90%
See 1 more Smart Citation
“…The IR spectra of compounds 4a-o displayed absorption bands around 3400 cm -1 for the indolic NH group in addition to the absorption bands of carbonyl groups near 1720 cm -1 which is consistent with the previously reported ones for compounds 4a [26] and 4f [27]. Also, their 1 H NMR spectra revealed a D 2 O-exchangeable signals in the region δ 10.84-11.01 ppm attributable to the NH protons of the indolin-2-one moieties, in addition to the signal of the methine protons (-CH = N-) in the region δ 8.55-8.70 ppm which is in accordance with those previously reported for compounds 4a [26], 4f [27] and 4i [28]. Moreover, the 13 C NMR spectra of compounds 4a-o showed signals resonating around δ 163 ppm, characteristic of C = O carbons.…”
Section: Results and Discussion Chemistrysupporting
confidence: 90%
“…All reagents and solvents were purified and dried by standard techniques. Compounds 4a [ 26 ], 4f [ 27 ], 4i [ 28 ] and 6a, b [ 29 ] have been previously reported. The microspheres were prepared with poly (D, L-lactide co-glycolide) PLGA (50:50, mol.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of 3-((substituted)benzylidene)hydrazono)indolin-2-one ( 4 ) was straightforward, as illustrated in Scheme 1 [ 36 , 52 ]. In the first step, a mixture of isatin ( 1 ) and hydrazine hydrate was refluxed in ethanol and isatin monohydrazone ( 2 ) was obtained in quantitative yields (~99%).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that tryptophan obtained from food sources is usually converted to indole by gastrointestinal bacteria, which is further oxidized in the liver by CYP450 to isatin, therefore, isatin is present as an endogenous molecule in humans [ 19 , 20 ]. Various substituents on the isatin nucleus displayed numerous biological activities [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], including antimicrobial activity[ 31 , 37 ], topoisomerase inhibitory activity [ 7 , 38 ], epidermal growth factor receptor (EGFR) inhibitory activity [ 39 ], inhibitory activities on histone deacetylase (HDAC) [ 40 , 41 ], carbonic anhydrase [ 42 , 43 , 44 ], tyrosine kinase [ 45 , 46 , 47 ], cyclin-dependent kinases (CDKs) [ 9 , 48 , 49 ], adenylate cyclase inhibition [ 50 ] and protein tyrosine phosphatase (Shp2) [ 51 ]. A number of isatin-based marketed drugs and potential anticancer agents [ 41 ] are illustrated in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Isatin (1H-indole-2,3-dione) and its derivatives can be used as the starting material for preparing quinazoline drugs (such as cinchophen). 1,2 These compounds demonstrate a diverse array of biological and pharmacological activities including anticonvulsant, 3 antibacterial, 4,5 antifungal, 6 antiviral, [7][8][9] and anticancer 10,11 properties.…”
Section: Introductionmentioning
confidence: 99%